SOSIALISASI MENGENAI PENTINGNYA VITAMIN CURCUMA PADA MURID SD NEGERI 2 PANUNGGALAN DI KABUPATEN GROBOGAN - Gigih Kenanga Sari; Faizatul Fitria Sofa; Febri Andika Rahma; Nadzia Putri Nur Afiana; Nike Wijayanti; Oktafia Resa Anggraini (LPPM AN Nuur, 2025)
Background: Vitamin and micronutrient deficiencies in children are among the major contributors to poor appetite, growth disturbances, and susceptibility to illness. Natural supplements such as Curcuma have been widely used due to their pharmacological benefits, including appetite stimulation and digestive support. Despite the availability of multivitamin products on the market, many are not affordable or suitable for specific nutritional needs, especially for children in lowerincome families. Aims: This community service program aimed to educate elementary school students at SD Negeri 2 Panunggalan about the importance of vitamins—particularly those derived from Curcuma—in supporting appetite and general health. The activity was also designed to promote early understanding of healthy nutrition and the benefits of herbal-based supplements. Results: The implementation consisted of several stages: preparation, educational sessions including interactive discussions, and evaluation through post-tests. The results showed that students could recognize different types of appetite-enhancing vitamins and understood the role of Curcuma in improving health. The educational intervention successfully increased students' awareness of vitamin use and the benefits of traditional herbal supplements. Conclusion: Early education on the benefits of herbal-based supplements like Curcuma is effective in promoting nutritional literacy among school-aged children. Community-based health education initiatives such as this can play a significant role in addressing childhood anorexia and micronutrient deficiencies, especially when led by university students as health education ambassadors.